2010
DOI: 10.1002/ana.21896
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal interictal spikes disrupt cognition in rats

Abstract: Objective-Cognitive impairment is common in epilepsy, particularly in memory function. Interictal spikes are thought to disrupt cognition, but it is difficult to delineate their contribution from general impairments in memory produced by etiology and seizures. We investigated the transient impact of focal interictal spikes on the hippocampus, a structure crucial for learning and memory and yet highly prone to interictal spikes in temporal lobe epilepsy.Methods-Bilateral hippocampal depth electrodes were implan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

15
138
2

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(159 citation statements)
references
References 50 publications
15
138
2
Order By: Relevance
“…interictal spikes impair fundamental neurobiological phenomena associated with memory formation and consolidation (12,13). These studies and others provided support for the idea that even brief episodes of epileptiform activity (e.g., interictal spikes) can impair memory.…”
Section: Coming Of Age: Seizures In Admentioning
confidence: 64%
“…interictal spikes impair fundamental neurobiological phenomena associated with memory formation and consolidation (12,13). These studies and others provided support for the idea that even brief episodes of epileptiform activity (e.g., interictal spikes) can impair memory.…”
Section: Coming Of Age: Seizures In Admentioning
confidence: 64%
“…One study 13 showed a 6% decline in working memory performance related to mesial temporal IED. However, as demonstrated in previous studies of cortical IED, 9,10 the degree of cognitive impact could have been underestimated since the authors did not consider 1) the precise timing of the IED within the memory task trials and 2) the specific components involved in memory processing.Using a rodent model of TLE, 14 we recently found that hippocampal IED were related to considerable decrements in short-term memory retrieval but not memory encoding or maintenance. Therefore, the cognitive impact of IED in the hippocampus may be substantially more important than previously documented.…”
mentioning
confidence: 99%
“…Using a rodent model of TLE, 14 we recently found that hippocampal IED were related to considerable decrements in short-term memory retrieval but not memory encoding or maintenance. Therefore, the cognitive impact of IED in the hippocampus may be substantially more important than previously documented.…”
mentioning
confidence: 99%
See 2 more Smart Citations